The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1093/geront/34.4.553
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Interactive Computer Services To Enhance the Quality of Life for Long-Term Care Residents

Abstract: This study examines and documents the effects of interactive computer-based education and training on the rehabilitation of long-term care residents. This approach was found to provide mental stimulation and challenge, as well as improving practical skills which directly impact upon the competencies and feelings of autonomy of the participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 0 publications
2
36
1
Order By: Relevance
“…People who are chronically ill or disabled tend to be socially isolated; the use of e-mail and the Internet would offer them an opportunity to take part in society once again. In addition, past research already found positive effects of Internet use on psychological wellbeing of older adults in institutional settings (McConatha, McConatha, & Dermigny, 1994White et al, 1999;. Therefore, we expect the Esc@pe project to be an effective intervention in combating loneliness in general and social loneliness in particular.…”
Section: Lonelinessmentioning
confidence: 88%
“…People who are chronically ill or disabled tend to be socially isolated; the use of e-mail and the Internet would offer them an opportunity to take part in society once again. In addition, past research already found positive effects of Internet use on psychological wellbeing of older adults in institutional settings (McConatha, McConatha, & Dermigny, 1994White et al, 1999;. Therefore, we expect the Esc@pe project to be an effective intervention in combating loneliness in general and social loneliness in particular.…”
Section: Lonelinessmentioning
confidence: 88%
“…In other studies computers have been introduced into homes for the elderly and these studies initially appear to suggest that the introduction of computers has a positive effect on elderly users' wellbeing (see for example, McConatha et al, 1994). In studies where interpersonal communication was offered, this was the most popular and widely used application among the elderly users (Danowski and Sacks, 1980;McConatha et al, 1994).…”
Section: Email: Previous Researchmentioning
confidence: 99%
“…In studies where interpersonal communication was offered, this was the most popular and widely used application among the elderly users (Danowski and Sacks, 1980;McConatha et al, 1994). Unfortunately these studies used standard commercial software, which necessitated a high level of support.…”
Section: Email: Previous Researchmentioning
confidence: 99%
“…This growth comes from two areas: an increase in the total number of people in the older adult category and in greater use of computers by older individuals. D. McConatha, J. McConatha, and Dermigny (1994) demonstrated that older adults frequently use on-line services, including email, games and puzzles, consumer reports, educational items, bulletin boards and stock market reports. These trends highlight the desire and ability of older persons to embrace technology.…”
mentioning
confidence: 99%